Pediatric Paroxysmal Exercise-Induced Neurological Symptoms: Clinical Spectrum and Diagnostic Algorithm - Danti, Federica Rachele; Invernizzi, Federica; Moroni, Isabella; Garavaglia, Barbara; Nardocci, Nardo; Zorzi, Giovanna (Frontiers in Neurology, 2021)
Paroxysmal exercise-induced neurological symptoms (PENS) encompass a wide spectrum of clinical phenomena commonly presenting during childhood and characteristically elicited by physical exercise. Interestingly, few shared pathogenetic mechanisms have been identified beyond the well-known entity of paroxysmal exercise-induced dyskinesia, PENS could be part of more complex phenotypes including neuromuscular, neurodegenerative, and neurometabolic disease, epilepsies, and psychogenetic disorders. The wide and partially overlapping phenotypes and the genetic heterogeneity make the differential diagnosis frequently difficult and delayed; however, since some of these disorders may be treatable, a prompt diagnosis is mandatory. Therefore, an accurate characterization of these symptoms is pivotal for orienting more targeted biochemical, radiological, neurophysiological, and genetic investigations and finally treatment. In this article, we review the clinical, genetic, pathophysiologic, and therapeutic landscape of paroxysmal exercise induced neurological symptoms, focusing on phenomenology and differential diagnosis.